2023
DOI: 10.1038/s41598-023-27936-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal distribution, trend, forecast, and influencing factors of transboundary and local air pollutants in Nagasaki Prefecture, Japan

Abstract: The study of PM2.5 and NO2 has been emphasized in recent years due to their adverse effects on public health. To better understand these pollutants, many studies have researched the spatiotemporal distribution, trend, forecast, or influencing factors of these pollutants. However, rarely studies have combined these to generate a more holistic understanding that can be used to assess air pollution and implement more effective strategies. In this study, we analyze the spatiotemporal distribution, trend, forecast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…While Sokhi et al [31] comprehensively analyzed the global data and reported a decrease of approximately 30% to 40% in mean PM2.5 concentrations during the 2020 full lockdown compared to the same period in 2015-2019, several studies conducted in East Asia showed more complex PM2.5 signals [27,28,29,30,32,52,53]. Literature also reports reductions in PM2.5 levels over outflow regions during the COVID-19 period [9,24,28,29,31,32]. Some studies have observed a rebound in PM2.5 levels in South Korea and the Pearl River Delta following the easing of COVID-19 restrictions [28,32], while other has reported continued reductions in PM2.5 levels in Japan in 2021 [9].…”
Section: Covid-19 Restrictionmentioning
confidence: 99%
See 4 more Smart Citations
“…While Sokhi et al [31] comprehensively analyzed the global data and reported a decrease of approximately 30% to 40% in mean PM2.5 concentrations during the 2020 full lockdown compared to the same period in 2015-2019, several studies conducted in East Asia showed more complex PM2.5 signals [27,28,29,30,32,52,53]. Literature also reports reductions in PM2.5 levels over outflow regions during the COVID-19 period [9,24,28,29,31,32]. Some studies have observed a rebound in PM2.5 levels in South Korea and the Pearl River Delta following the easing of COVID-19 restrictions [28,32], while other has reported continued reductions in PM2.5 levels in Japan in 2021 [9].…”
Section: Covid-19 Restrictionmentioning
confidence: 99%
“…Transboundary air pollution resulting from winter monsoon-driven continental outflows has 35 raised significant environmental concerns in downwind areas such as South Korea [4,5,6,7], Japan [3,7,8,9,10,11], Taiwan [12,13,14,15,16], and Hong Kong [14,17,18,19]. In eastern China, satellite-based estimates of PM2.5 show consistent long-term trends with some variations in interannual patterns among subregions (Fig.…”
mentioning
confidence: 94%
See 3 more Smart Citations